Ginkgo Biloba Extract Reduces Cardiac and Brain Inflammation in Rats Fed a HFD and Exposed to Chronic Mental Stress through NF-κB Inhibition - Lijun Zhang; Guo Li; Shuhui Tao; Pengyan Xia; Naveed Chaudhry; Shawn Kaura; Sara Saymuah Stone; Meiyan Liu (Hindawi Limited, 2022)
Background. Cardiac and brain inflammation can lead to a host of deleterious health effects. Our formal experimental research showed that Ginkgo Biloba Extract (GBE) contributed to the reduction of inflammation in mice with myocardial infarction along with depression. This study is aimed at expanding on these findings via analysis of the cardiac and brain inflammation, which was prevented by GBE in rats suffering with a high-fat diet (HFD) combined with unpredictable chronic mild stress (UCMS). Methods. Fifty male Wistar rats were randomly divided into 5 groups treated with normal diet, UCMS, HFD, HFD+UCMS, or HFD+UCMS+GBE respectively. Rats treated with HFD were fed a high-fat diet for 10 or 13 weeks. Rats treated with UCMS were exposed to 8 types of chronic physical and psychological stressors for 10 or 13 weeks. The HFD+UCMS+GBE group was given GBE via intragastric gavage for 8 consecutive weeks. Sucrose preference was established for the assessment of depressive behaviors. The heart function was evaluated by echocardiography. The rats were terminated at the end of the 10th or 13th week. The blood was used for detecting low-density lipoprotein cholesterol (LDL-c) and total cholesterol (TCHO) by the kit instructions; Helper T Lymphocytes (TH cells, CD3+CD4+) by flow cytometry; and Interleukin- (IL-) 1β, IL-37, IL-38, NT-proBNP, hs-cTNI, and Ischemia-modified albumin (IMA) by enzyme-linked immunosorbent assay (ELISA). The cardiac tissues were used for detecting IL-1β, nuclear factor kappa B (NF-κB), inhibitor molecule protein (IκB), and IL-1 receptor (IL-1R) by ELISA and P65, P-P65, IκB, and phosphorylated inhibitor molecule protein α (P-IκBα) for western blotting. Cortex tissues were used for detecting 8-iso-prostaglandinF2α (8-iso-PGF2α) by ELISA. Oil Red staining was carried out to evaluate the lipid deposits in the rats' aortic arteries. Sirius Red staining was performed to display collagen fibers in the arteries. Hematoxylin and Eosin (HE) staining was applied to reveal pathological changes to arteries and cardiac tissue. Immunohistochemical staining was employed to assess the distribution of inflammatory cytokine IL-1β in arteries and cardiac tissues. Transmission Electron Microscopy (TEM) was performed to observe the ultrastructure of hippocampal cornu ammonis (CA)1 (CA1) neurons. Results. In the rats with HFD+UCMS+GBE, over 13 weeks, GBE exerted a protective role of both the heart and brain, by attenuating cardiac inflammation and brain oxidative stress. Levels of Helper T lymphocytes and serum anti-inflammatory cytokines involving IL-37 and IL-38 were all elevated, and the depressive behaviors of HFD+UCMS rats were attenuated by GBE. This protective role was accomplished via inhibition of the canonical NF-κB signaling pathway, through downregulation of the expressions of P-P65 and P-IκB-α in the heart, hippocampus, cortex, and hypothalamus. Conclusions. This study suggests that GBE poses a protective role from the various pathologies associated with high-fat diets, unpredictable chronic mild stress, and depression, possibly via improving peripheral immunity and reducing cardiac and brain inflammation.